Pengaruh Work Stress dan Workplace Bullying yang Dimediasi Job Burnout Terhadap Turnover Intention - Haria, Wilhelmus Alfred; Tanuwijaya, Justine (Universitas Bunda Mulia, 2026)
This study aims to analyze the influence of job stress and workplace bullying on turnover intention, with job burnout as a mediating variable, among employees of PT Bank Central Asia Tbk in the Jakarta area. The research employed a quantitative method through a survey by distributing questionnaires to 340 employees, while hypothesis testing was conducted using the Structural Equation Modeling (SEM) method. The findings indicate that job stress has no positive effect on turnover intention or job burnout, whereas workplace bullying has a positive effect on both. Furthermore, job burnout was found to have a positive effect on turnover intention. It does not mediate the relationship between job stress and turnover intention but serves as a partial mediator in the relationship between workplace bullying and turnover intention. From a managerial perspective, the results highlight the importance of creating a healthy work environment by managing workloads in line with employees’ capacity, providing training to enhance competencies, and strengthening social support from supervisors and colleagues.